Kontribusi Trait Psychopathy dari Dark Triad Personality Terhadap Moral Disengagement Residivis di Lapas Kelas 1 Kota Makassar - Devnet Vicente; Istianah Tadjuddin; A. Juwita Am (Asosiasi Psikologi Forensik (Apsifor), 2023)
Criminal offender are categorized into two categories, namely one time offender and repeat offenders or recidivists. There are two main predictors of repeat offenders : individual and external. Individual factors such perpetrator’s moral judgement, namely moral disengagement. Several studies in prison populations have succeeded in examining predictors of moral disengagement, one of which is personality. High impulsive tendencies and low levels of empathy characteristic are commonly correlated with repeat offenders. This tendency is in accordance with the characteristics of the psychopathy trait from Dark Triad Personality group. This research aimed to investigate the contribution of psychopathy trait from the Dark Triad Personality to the Moral Disengagement of Recidivists in Class I Prisons in Makassar City. This research uses quantitative methods and is analyzed using linear regression analysis techniques. This research sample used a total sampling involving 128 recidivists detained in Makassar Class I Penitentiary as of May 20 2023. The results showed psychopathy traits contributed 31.7% (p = 0.000; r = 0.567) to the moral disengagement of recidivists in Makassar City Class I Penitentiary. Additional analysis in this study found an unique relationship between two variables are discussed.